Jesus Walks on the Sea - James Tissot (Wikimedia Commons, 1886)
Notice iconographique issue de Wikimedia Commons. Titre: Jesus Walks on the Sea.
Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons